Analisis Peran Financial Technology dan Uang Elektronik dalam Meningkatkan Inklusi Keuangan di Indonesia - Nasywa Aurellia Salsabila; Khoirul Umam; Nuruddin (Jurnal Riset Multidisiplin Edukasi, 2026)
The development of financial technology (fintech) and electronic money (e-money) in Indonesia has significantly impacted the increase of financial inclusion through faster, more practical, and efficient access to digital-based financial services. The purpose of this study is to analyze the role of financial technology (fintech) and electronic money (e-money) in increasing financial inclusion in Indonesia and their impact on consumer behavior. The method used in this study is a qualitative approach with a literature review, namely by examining various scientific sources in the form of journals, reports, and related publications relevant to the research topic. The results of this study indicate that fintech and e-money play a significant role in increasing financial inclusion through accessibility, transaction process efficiency, and expanding access to public financial services. At the same time, both innovations can encourage public involvement in the digital financial system despite facing challenges such as low digital literacy levels, limited infrastructure, and data security risks. In addition, fintech and e-money, which make transactions easier, also increase the potential for improving consumer behavior, especially due to accessibility, digital promotion, and cashless payments that lead to reduced spending control. Therefore, it is necessary to increase the level of digital financial literacy and regulate the use of fintech and e-money to ensure the effective use of this technology in supporting financial inclusion.